PARALELISME TOKOH RASUS DAN PAMBUDI DALAM DUA KARYA AHMAD TOHARI RONGGENG DUKUH PARUK DAN DI KAKI BUKIT CIBALAK - Nirmalawati, Widya; Fauzan, Akhmad; Khristianto, NFN (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2023)
This study aims to describe the parallelism of the male characters Rasus in the novel Ronggeng Dukuh Paruk and Pambudi in the novel Di Kaki Bukit Cibalak by Ahmad Tohari. The method used in this research is textual research, which uses text in the novel to understand and interpret the text to connect the text to a broader social, political, and cultural. The results of the study, both male characters, Rasus and Pambudi, moved from a traditional environment to a more modern one, namely the city. Mobility became the driving force for transformation into a new individual. However, each of the stories' male protagonists' indecisiveness turns out to be a weakness. Rasus struggles with his